The expression of Lin28B was co-regulated by H3K4me2 and Wnt5a/β-catenin/TCF7L2 - Ya-ni ZHANG; Cai HU; Ying-jie WANG; Qi-sheng ZUO; Bi-chun LI (Journal of Integrative Agriculture, 2020)
Lin28A and Lin28B are homologous RNA-binding proteins that participate in the development of primordial germ cells. The mechanisms underlying expression and regulation of Lin28A have been well documented, but such information for Lin28B is limited. In this study, a fragment of the Lin28B promoter was cloned, the pEGFP-pLin28B vector was constructed. DF-1 chicken fibroblasts were transfected and the expression of green fluorescent protein (GFP) was measured. Furtherly, Lin28B promoter of different lengths fragments was cloned using the chromosome-walking method and the fragments were ligated into the PGL3-Basic vector, and transfected into DF-1 cells. Results of dual-luciferase reporter assay showed that the core of the Lin28B promoter was included in the sequence from –1 431 to –1 034 bp. The binding sites of the transcription factor TCF7L2 was showed within this sequence by bioinformatics analysis. The promoter activity of Lin28B was downregulated (P<0.05) when the TCF7L2 binding site was mutated. Further experiments suggested that Lin28B promoter activity responded to the activation or inhibition of Wnt signaling. Results of chromatin immunoprecipitation and quantitative PCR showed that β-catenin-TCF7L2 may be enriched in the Lin28B promoter core area. In vivo and in vitro activation or inhibition of Wnt signaling significantly up- or down-regulated (P<0.05) Lin28B expression. H3K4me2 enriched in the promoter of Lin28B, which affected the regulation of Wnt signaling to Lin28B. In conclusion, our results showed that H3K4me2 and Wnt5a/β-catenin/TCF7L2 were the positive regulators of Lin28B expression. Findings of this study may lay a theoretical foundation for illuminating the mechanism underlying Lin28B expression.